IMPACT OF CERTAIN DEMOGRAPHIC CHARACTERISTICS ON CONSUMER ATTITUDES ABOUT ORGANIC AGRICULTURAL AND FOOD PRODUCTS IN THE REPUBLIC OF SERBIA - Bojan Dimitrijević; Jelena Golijan - Pantović; Nada Lakić; Slavoljub Lekić; Branka Bulatović; Zoran Rajić; Sreten Jelić (Ekonomika Poljoprivrede (1979))
The main objective of this paper is to examine the attitudes and opinions of respondents about organic agricultural and food products, as well as motives for buying this type of products, depending on their gender, education and age, because it is assumed that they have the strongest influence on consumer attitudes. Data were obtained through survey questionnaires, on the territory of the Republic of Serbia. The research was conducted on a random sample of 369 respondents. The Chi square independence test was used to study the set assumptions. The results of the research indicated that the analysed demographic factors had certain influence on the opinion and attitudes of the respondents about ecological agricultural and food products, as well as on the motives for their use.